The madstone : a novel - Crook, Elizabeth, 1959- (Little, Brown and Company, 2023)
"Texas hill country, 1868. As nineteen-year-old Benjamin Shreve tends to business in his workshop, he witnesses a stagecoach strand a passenger. When the man, a treasure hunter, persuades Benjamin to help track down the vanished coach--and a mysterious fortune left aboard--Benjamin is drawn into a drama whose scope he could never have imagined, for they discover on reaching the coach that its passengers include Nell, a pregnant young woman, and her four-year-old son, Tot, who are fleeing Nell's brutal husband and his murderous brothers. Having told the Freedmen's Bureau the whereabouts of her husband's gang--a sadistic group wanted for countless acts of harassment and violence against Black citizens--Nell is in grave danger. If her husband catches her, he will kill her and take their son. Learning of their plight, Benjamin offers to deliver Nell and Tot to a distant port on the Gulf of Mexico, where they can board a ship to safety. He is joined in this chivalrous act by two other companions: the treasure hunter whose stranding began this endeavor and a restless Black Seminole who is a veteran of wars on both sides of the Rio Grande and who has an escape plan of his own.​ Fraught with jeopardy from the outset, the trek across Texas becomes still more dangerous as buried secrets, including a cursed necklace, emerge. And even as Benjamin falls in love with Nell and imagines a life as Tot's father, vengeful pursuers are never far behind. With its vivid characters and expansive canvas, The Madstone calls to mind Lonesome Dove, yet Elizabeth Crook's new novel is a singular achievement. Told in Benjamin's resolute and unforgettable voice, it is full of eccentric action, unrelenting peril, and droll humor--a thrilling and beautifully rendered story of three people sharing a hazardous and defining journey that will forever bind them together"--